Teaching module electrical power systems /c Mohd Redzuan Ahmad, Ruhaizad Ishak - Mohd. Redzuan Ahmad; Ruhaizad Ishak (Penerbit Universiti Malaysia Pahang, 2011)
This teaching module purposely prepared to facilitate the learning process of the electrical power systems course which offered to undergraduate student